Handbook of sports and lottery markets - Hausch, Donald B.; Ziemba, W. T. (Handbooks in finance., 2008)
Its basic empirical research and investigation of pure theories of investment in the sports and lotto markets make this volume a winner. With new overviews of scholarship on the industry side of racetrack and other betting markets to betting exchanges and market efficiencies, contributors consider a variety of sports in countries around the world. The result is not only superior information about market forecasting, but macro- and micro-analyses that are relevant to other markets as well. * Major focus on the variety of market efficiencies * Significant coverage of sports from racing to jai alai. * New studies of betting exchanges and internet wagering markets.